2022
DOI: 10.1186/s12879-022-07260-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of schistosomiasis and soil-transmitted helminths on expressive language skills among African preschool children

Abstract: Background Schistosomiasis and soil transmitted helminths (STH) have been associated with compromised child development. We determined the effect of schistosomiasis and STH on expressive language skills among isiZulu speaking preschool children focusing on the variables: age, gender, school and stunting. Methods We quantitatively compared the performance of a cohort of infected and non-infected children using a 2 phased approach. In phase 1 infecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…In line with the present findings, Patrick et al (2005;Pinkerton et al, 2016) found that, in children with heavy burdens of early childhood diarrhea, impairments in semantic, but not phonetic, fluency were observed after controlling for maternal education, breastfeeding, and child schooling. Mazibuko and Chimbari (2022) found that schistosomiasis and other STHs were correlated with lower expressive language scores. Such impacts on semantic and semiotic aspects of language are important, given the role of language in the development of higher thought (Frawley, 1996;Vygotsky, 2012).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In line with the present findings, Patrick et al (2005;Pinkerton et al, 2016) found that, in children with heavy burdens of early childhood diarrhea, impairments in semantic, but not phonetic, fluency were observed after controlling for maternal education, breastfeeding, and child schooling. Mazibuko and Chimbari (2022) found that schistosomiasis and other STHs were correlated with lower expressive language scores. Such impacts on semantic and semiotic aspects of language are important, given the role of language in the development of higher thought (Frawley, 1996;Vygotsky, 2012).…”
Section: Discussionmentioning
confidence: 94%
“…Indeed, in children with heavy burdens of early childhood diarrhea, impairments in semantic, but not phonetic, fluency were observed after controlling for maternal education, breastfeeding, and child schooling (Patrick et al, 2005). Likewise, while schistosomiasis STHs were not related to language impairments during diagnosis, STHs were correlated with lower expressive language scores 12 weeks later (Mazibuko & Chimbari, 2022).…”
mentioning
confidence: 99%
“…Continued assessment of the safety of PZQ constitutes an important aspect of maintaining its availability (as the best chemotherapy) and public acceptability, which is invariably crucial to achieving the ambitious elimination targets. Also, schistosomiasis has been shown to significantly impact children's education due to its effects on health and cognitive development [31][32][33][34][35][36]. All efforts geared towards addressing this disease thus contribute to creating a better learning environment for children and ensuring universal access to quality education-SDG 4, target 4a.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, an alarming 20 million individuals yearly require treatment for schistosomiasis (5). These parasitic infections disproportionately affect vulnerable populations, especially children, and perpetuate a cycle of poverty, impaired cognitive development, and reduced school attendance (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%